2013
DOI: 10.1111/anec.12106
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Continuous Positive Airway Pressure Therapy on Atrial Electromechanical Delay and P‐Wave Dispersion in Patients with Obstructive Sleep Apnea

Abstract: Our findings suggested that CPAP therapy provides more homogenous conduction through atria in patients with OSA. This effect may translate into decreased risk for AF associated with OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 32 publications
(33 reference statements)
0
21
0
1
Order By: Relevance
“…The impact of CPAP therapy on atrial electromechanical delay and P‐wave dispersion was previously studied in OSAS identifying a relation with the severity of the disease and the level of hypoxia . Bayir et al . showed that increased inter‐ and intra‐atrial electromechanical delays and prolonged Pmax and PD are evident in OSAS patients, and improvement in these AF risk markers as well as in diastolic LV function could be obtained after effective CPAP therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of CPAP therapy on atrial electromechanical delay and P‐wave dispersion was previously studied in OSAS identifying a relation with the severity of the disease and the level of hypoxia . Bayir et al . showed that increased inter‐ and intra‐atrial electromechanical delays and prolonged Pmax and PD are evident in OSAS patients, and improvement in these AF risk markers as well as in diastolic LV function could be obtained after effective CPAP therapy.…”
Section: Discussionmentioning
confidence: 99%
“…in a study comparing tissue Doppler echocardiography and electrophysiological study found a moderate correlation between intra‐left atrial conduction time detected by tissue Doppler echocardiography (ILCT‐echo) and by electrophysiological study (ILCT‐eps), and demonstrated that tissue Doppler echocardiography was a reliable technique for the measurement of atrial electromechanical delay. Previous studies have demonstrated that prolonged intra‐ and inter‐atrial conduction times and inhomogeneous propagation of sinus impulses would be the characteristics of increased AF risk in various clinical conditions during sinus rhythm . It has been studied in some clinical conditions, and it was found that AEMD is significantly correlated with the prolonged maximum P‐wave duration, P‐wave dispersion, and degree of histopathological changes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Studies have shown that the high rate of AF in OSAS patients indicates the co-occurrence of these two conditions. [24][25][26][27] However, the exact mechanism of AF predisposition in OSAS patients remains unknown. Prolonged intra-and inter-atrial conduction times and inhomogeneous propagation of sinus impulses are common electrophysiological features in AF cases.…”
Section: Discussionmentioning
confidence: 99%
“…Both systolic and diastolic abnormalities in patients with OSA can be reversed as early as after three months of CPAP therapy, with progressive improvement in cardiovascular remodeling over one year [76]. Additionally, CPAP therapy provided more homogenous conduction through atria in patients with OSA [77].…”
Section: Cpap and Cardiac Remodelingmentioning
confidence: 99%